2020
DOI: 10.1002/mds.28396
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cholesterol in α‐Synuclein and Lewy Body Pathology in GBA1 Parkinson's Disease

Abstract: A BS TRACT: Parkinson's disease (PD) is a progressive neurodegenerative disease where dopaminergic neurons in the substantia nigra are lost, resulting in a decrease in striatal dopamine and, consequently, motor control. Dopaminergic degeneration is associated with the appearance of Lewy bodies, which contain membrane structures and proteins, including α-synuclein (α-Syn), in surviving neurons. PD displays a multifactorial pathology and develops from interactions between multiple elements, such as age, environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 222 publications
0
29
0
Order By: Relevance
“…The human brain is composed of 25% cholesterol, and its dysregulation caused by oxidative stress and/or inflammation can further contribute to α‐synuclein trafficking, leading to PD progression (Pingale & Gupta, 2021). Recently, the cell experiments performed by García‐Sanz et al (2018, 2021) proposed that the accumulation of cholesterol in the lysosomes caused by a mutation in GBA1 (the gene encoding glucocerebrosidase)‐induced PD or glucocerebrosidase deficiency might indirectly increase the levels of α‐synuclein by compromising lysosomal activity and altering cholesterol levels in the lipid raft.…”
Section: Oxysterolsmentioning
confidence: 99%
“…The human brain is composed of 25% cholesterol, and its dysregulation caused by oxidative stress and/or inflammation can further contribute to α‐synuclein trafficking, leading to PD progression (Pingale & Gupta, 2021). Recently, the cell experiments performed by García‐Sanz et al (2018, 2021) proposed that the accumulation of cholesterol in the lysosomes caused by a mutation in GBA1 (the gene encoding glucocerebrosidase)‐induced PD or glucocerebrosidase deficiency might indirectly increase the levels of α‐synuclein by compromising lysosomal activity and altering cholesterol levels in the lipid raft.…”
Section: Oxysterolsmentioning
confidence: 99%
“…Indeed, 24S-OHC is able to protect neurons from the cytotoxicity of 7-ketocholesterol, inducing their adaptations, as well as reducing Aβ accumulation and tau hyperphosphorylation. On the other hand, the same molecule seems to induce cell apoptosis favoring the activity of caspase proteins, leading to the formation of abnormal lipid structures, and increasing oxidative stress [ 110 , 111 , 112 , 113 , 114 ].…”
Section: Cholesterol Synthesis and Metabolism In The Cnsmentioning
confidence: 99%
“…Cholesterol metabolism also seems to be involved in PD pathogenesis: cholesterol excess in lysosomes leads to abnormalities in the lipid rafts, which are membrane microdomains enriched in cholesterol and sphingolipids [ 111 ]. As a consequence, altered interactions between cholesterol and α-syn occur in brain cells, enhancing α-syn oligomerization and thus influencing PD pathogenesis [ 112 ]. Causes of this excess of cholesterol inside lysosomes could be mutations that occur in the GBA1 gene that encodes for the lysosomal enzyme β-glucocerebrosidase-1 and are shown to correlate with PD.…”
Section: Cholesterol Synthesis and Metabolism In The Cnsmentioning
confidence: 99%
“…Therefore, searching for biomarkers related to the risk and severity of PD has become a hot spot in clinical research in recent years. In recent years, blood lipids have become a blood biochemical index that may be related to PD in many clinical studies [ 41 , 42 ], but the results of the studies are not consistent. The results of our synthesized outcomes have indicated that the TC, TG, HDL-C, and LDL-C level in the PD patients was significantly lower than that of health controls.…”
Section: Discussionmentioning
confidence: 99%